Feasibility Test of Picture Book Recognizing the Dangers of Smoking as a Media for Educating Children about The Dangers of Smoking - Firda Atika Awaliya Putri; Nafikadini, Iken; Dewi Rokhmah (Universitas Airlangga, 2024)
Introduction: The picture book media 'Recognizing the Threat of Smoking' as education about the dangers of smoking for children. The theme used in the picture book media is the danger of smoking, which was appropriately given to children, especially those in grades 4-6 of elementary school, with an age range of 10-12 years old. Objective: The general aim of this research was to test the feasibility of the picture book as a media for educating children about the dangers of smoking. Methods: This research was a research and development study with a qualitative approach conducted in January 2021 in Jember Regency. Data collection was done through interviews, observations, and documentation. Data analysis used Thematic Content Analysis. Results: This picture book consists of 18 pages, created through four stages: starting from the synopsis made directly by the researcher, creating a storyline also done directly by the researcher. Followed by a colleague as an illustrator for creating digital images, and a digital book is also done by the illustrator, then the final stage is printing done by the researcher. Conclusion: The material presented in the picture storybook about the dangers of smoking to children was suitable for children to read, but there were suggestions regarding the exposure of information on the health effects of smoking, which was considered insufficient. It was feared that if the health effects of smoking were only limited to a few diseases, the educational message would be less effective for children, who might think that smoking only causes minor health issues.